Suitability pre-assessment for decoupling in-sewer captured streams to support urban blue-green climate adaptation measures. Issue 4 (18th March 2022) - Prenner, F.; Müller, H.; Stern, P.; Holzer, M.; Rauch, H. P.; Kretschmer, F.
Abstract: The application of nature-based solutions for climate change adaptation in cities has increased in recent years. To improve microclimatic conditions and to preserve the natural components of related assets, water supply is necessary. As an alternative to drinking water, stream water might serve as a natural source for irrigation. However, due to continuous urbanisation, water courses have often been banned underground in pipes or integrated in the combined sewer network, both making them not directly available for further usage. This article focuses on the perspectives of decoupling captured streams from underground infrastructure to support nature-based urban climate adaptation measures. It introduces a method to identify suitable locations for practical implementation considering the hydrological potential of the stream and the urban microclimatic sensitivity of the concerned area. The approach was applied in a case study in the north-western part of Vienna, including 16 streams with a total length of about 39 km covering an area of approximately 95 km 2 with about half a million inhabitants. This work proved the general practicality of the suggested method. It also revealed that about one-third of the investigated stream lengths appears high or medium suitable to support climate adaption measures, leading to notable cost savings for irrigation (for the substitution of drinking water) and wastewater treatment. Concluding, the decoupling of captured streams could contribute to a more sustainable and nature-based urban water management. The introduced method for suitability pre-assessment is applicable with rather easily available input data, which makes it transferable to other cities. HIGHLIGHTS: In-sewer captured stream water provides a possible water source for nature-based urban climate adaptation measures. The proposed method supports the evaluation of hydrological potential and urban microclimatic sensitivity. The application on the case study of Vienna reveals promising results. Results of the pre-assessment method act as a strategic guidance and decision support for practical implementation. Graphical Abstract